Experimental study on a fresh air heat pump desiccant dehumidification system using rejected heat. (October 2020) - Chai, Shaowei; Zhao, Yao; Ge, Tianshu; Dai, Yanjun
Highlights: Isothermal dehumidification can be realized by this system using rejected heat. Most of the cooling provided by the system is used for dehumidification. The COP of the system can be improved by 13–40% under experimental conditions. The moisture removal per kWh is 1.60–2.88 times that of the traditional method. Abstract: Desiccant coated heat exchanger (DCHE) was proposed for highly efficient dehumidification process due to the adsorption heat could be eased by inner cooling during the sorption process. Meanwhile, heat pump is probably used with DCHE together in humidity control processes because cooling and heating generated by vapor compression heat pump system match with the energy demand of DCHE well. A fresh air heat pump desiccant dehumidification system using rejected heat with desiccant coated heat exchanger (DCHE) was set up and experimentally tested in this paper. Near isothermal dehumidification process could be realized due to the utilization of DCHE which could convert the sensible cooling provided by vapor compression heat pump subsystem to latent cooling to increase the moisture removal of the system. The optimal average moisture removal and COP are 7.02 g/kgDA and 4.10, respectively, under the near ARI humid condition. Most of the total cooling generated by vapor compression heat pump subsystem is used for dehumidification. The moisture removal per kilowatt hour electric power consumption of the system is 1.60–2.88 times that of conventional condensation dehumidification method.